The Impact of Social Media in the Library Service - C, Kasimani.; K, Kasilingam. (International Journal of Information Studies, 2025)
Every one of the individual in the world deep fall down in a medium to communicate with people in remote areas. The people using the social media in India will increase day by day. In the current social media tools have become important communication tools for attract everyone with its unique features of update information. The social media users can share their ideas, feelings, images, documents, videos, with others through social media tools like as Whatts up , facebook, twitter and etc. This paper conveys library services though the social media.